Molecular control of plant shoot architecture (by Agustin Zsögön and Lázaro Eustáquio Pereira Peres). Issue 12 (8th March 2019) - Unknown
Abstract: Like in animals, the growth rate and pattern of plants is controlled by both genetic and environmental factors. Manipulation of plant form and height has been instrumental in the domestication and improvement of crops. The balance between growth of vegetative (stems, branches, leaves) and reproductive (flowers, fruits, seeds) organs in the shoot is of chief importance for agriculture. In this Teaching Tool we present an overview of recent advances in understanding the molecular basis of shoot architecture. We introduce basic concepts of plant growth and shape generation and provide an overview of their control. Both chemical and physical forces are involved in pattern generation. Plant hormones, transcription factors and small RNAs are key among the former, tension and pressure among the latter. We discuss how physical forces interact with chemical signals to produce specific developmental outcomes. Plants can concentrate their growth in the vertical direction, or laterally, through profuse side branching and branch outgrowth, and we present a brief outline of the molecular and physiological mechanisms involved in vertical and lateral growth. Finally, we outline the potential for manipulation of plant architecture using state-of-the-art genome editing technology and how it could bring about agricultural benefits through an accelerated optimization of crop shape and size. (Posted January 15, 2019) Click HERE to access Teaching Tool Components RECOMMENDED CITATION STYLE: Zsögön, A. and Peres, L.E.P.) (January 15, 2019). Molecular control of plant shoot architecture. Teaching Tools in Plant Biology: Lecture Notes. The Plant Cell (online), doi/ /10.1105/tpc.118.tt1218.